Figurative Language in Student Poetry: An Analysis of Eighth-Grade Students’ Poems at MTs Ja-Alhaq Bengkulu - Ahmad Ibrahim (Yayasan Darussalam Bengkulu, 2024)
Figurative language plays a crucial role in enriching poetic expression and developing students’ literary competence, yet its systematic use among junior secondary school students in Indonesia has not been widely documented. This study aimed to analyze the types and functions of figurative language found in a collection of poems written by eighth-grade students at MTs Ja-Alhaq, Bengkulu City. Employing a qualitative descriptive design, the data were collected through documentation of student-written poems and analyzed using semantic and stylistic approaches to identify and classify figurative devices. The analysis revealed frequent use of simile, hyperbole, personification, and repetition, which functioned to emphasize emotional intensity, convey abstract ideas, and enhance the aesthetic quality of the texts, while other devices such as metaphor, allegory, and ellipsis appeared less frequently. These findings suggest that students at the junior secondary level are capable of applying diverse figurative forms, reflecting both creativity and emerging literary awareness. The novelty of this research lies in its empirical focus on adolescent poetry within an Indonesian educational context, an area rarely explored in previous studies. The results imply that integrating figurative language instruction into the language learning curriculum can enhance students’ creativity, critical thinking, and appreciation of literature, while also contributing to the broader development of literacy and character education.